Chlamydia trachomatis infection in patients selected for HPV detection - Santo, I. (2012)
Background: The significance of the association between the human papillomavirus (HPV) and other sexually transmitted infections in the development of cervical, penile or anal neoplasias has been investigated, and the more consistent data have pointed to an association with Chlamydia trachomatis. In Portugal, the lack of information on STI precludes any knowledge on this subject. Objective: To determine CT infection in a group of individuals selected for HPV detection in the major Portuguese STD clinic. Methods: This opportunistic screening comprehended 177 outpatients (148 women, 29 men; age: 16-61 years) suspected of HPV infection (warts, abnormal histology) between 2008 and 2010. Demographic and sexual behaviour data and a full medical history were obtained at enrolment. Genital samples (cervical, vulvar, vaginal, penile or anal) were collected from all the subjects. HPV DNA was detected by CLART HPV2 assay, which allowed the detection of 35 genotypes. CT DNA was detected by Cobas 4800. Results and Discussion: Overall, 84.5% of the individuals had at least one of the infections. Evidencing an excellent correlation with clinical signs, HPV infection was detected in 68.2% of the women and in 75.9% of the men, where CT positivity was 10.1% and 13.8%, respectively. Coinfection was observed in 8.9% of the women and in 13.8% of the men. No correlation with HPV or CT genotypes could be established. HPV infection was more frequent in CT negative (87.1%) than in CT positive women (13.8%), and the same was observed for men (81.8% versus 18.2%). Full results will be presented and discussed. Conclusions: No correlation between HPV-CT coinfection, and clinical signs was observed. However, further long-term studies are needed to elucidate the effects of HPV-CT coinfection in the clinical history of the infected patient, which would greatly contribute towards a better management of patients.